AB0807 Comparative survey of rheumatology training including uk, singapore, malaysia and new zealand. (23rd January 2014) - Das, P.; Moorthy, A.; Chapman, P.; Suresh, E.; Sakthiswary, R.
Abstract : Background: Rheumatology is an emerging medical speciality. With the growing interest more trainees are choosing rheumatology as their speciality of interest. Interestingly, trainees often prefer to migrate to different countries during or after completion of their training because of various reasons eg better job opportunities or socio-economic reasons. Hence it is important to have a comparable training curriculum across these countries 1 . This study was designed to compare the existent training curriculum in rheumatology amongst UK and other countries including New Zealand, Singapore and Malaysia. Objectives: To compare the rheumatology training curriculum amongst UK, New Zealand, Malaysia and Singapore. Methods: This is a prospective observational questionnaire based study. An online survey consisted of 39 questions has been designed which was piloted locally and redesigned accordingly. The questionnaire was circulated electronically to all the rheumatology trainees across UK and New Zealand, Malaysia and Singapore. Our survey was directed towards exploring different aspects to rheumatology training curriculum eg curriculum content, mode of delivery, training monitoring and job opportunities. The results were analysed using special software through smart survey. Results: Total respondents were n=60 including 16% (40/240) of UK trainees, 75% (9/12) from New Zealand, 45%(9/20) from Malaysia and 66%(3/5) ot Singapore trainees. It showed female predominance (55% of trainees). Fifty one percent of the trainees are doing combined training in rheumatology and internal medicine. The duration of rheumatology training was 3 years in Singapore, Malaysia and New Zealand and 5 years in UK Trainees from UK, Singapore and Malaysia had regular weekly in-house institutional training. Comparatively UK and Singapore trainees had more regular supervised training for large and small joint injections. Musculoskeletal ultrasound is an essential part of rheumatology training, however, only 26% of UK trainees, 20% of Singapore, Malaysian trainees and 8 % of New Zealand trainees had regular supervised training in musculoskeletal ultrasound. Both combined clinics and speciality clinics were more practised in UK centres, compared to other countries. Only 28% of UK trainees were actively participating in research, whereas 78% of respondents across all these countries were involved in local research projects. Speciality exit exam is mandatory for UK and Singapore trainees. 79% of UK and New Zealand trainees were fairly confident in taking up a consultant job although they found it difficult to get one. Consultant jobs were guaranteed for Malaysian trainees and easily available for Singapore trainees. Conclusions: There are no previous studies comparing rheumatology training between UK and other countries. Our study has shown that rheumatology training in UK appears more structured and supervised. Although it is difficult to harmonise rheumatology training between countries, this study provides useful initial data to further explore and optimise advanced rheumatology training in these different countries. References: Speciality training curriculum for rhaumatology. August 2010. Jount Royal college of physicians Training board. Disclosure of Interest: None Declared